Entrepreneurship, college, and credit: The golden triangle - SAMANIEGO, Roberto M. (Institutional Knowledge at Singapore Management University, 2018)
We develop a model to evaluate the aggregate impact of college finance in an environment with entrepreneurship. The calibrated model captures the stylized fact that entrepreneurs with college are more common and more profitable in the United States. The calibration indicates this is mainly because higher labor earnings allow college‐educated agents to ameliorate credit constraints if and when they eventually become entrepreneurs. Changes in financing constraints on entrepreneurs can thus affect college attendance, and changes in financing constraints on college can affect entrepreneurship rates as well.